Marketing Effectiveness Through Community at PT Naruna Karya Bersama: Efektivitas Pemasaran Melalui Komunitas Di PT Naruna Karya Bersama - Trya Malitasari; Muhadjir Anwar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This society service examines the implementation of community-based marketing strategies by PT Naruna Karya Bersama through the digital platform Komunitas Demi Anak. This marketing strategy aims to increase brand awareness, strengthen customer engagement, and convey product information organically. The society service method involved the use of a qualitative descriptive approach through observation, documentation, and unstructured interview methods during the internship. The results showed that the community plays an important role in building emotional relationships between companies and consumers. Routine activities such as kulwap (WhatsApp lectures), quizzes, and discussions are considered to be able to encourage members' understanding of parenting patterns, while strengthening the company's image as an educational partner. The existence of the community also facilitates the promotion process without a one-on-one personal approach, making it more efficient. However, there are still obstacles in the form of limited implementation time and suboptimal member participation. In general, community-based marketing is considered effective for start-up companies such as PT Naruna Karya Bersama and has the potential to become a long-term strategy in building customer loyalty.